Uji Validitas Media Papeda Berbasis Permainan Ular Tangga Untuk Meningkatkan Pemahaman Materi Bangun Datar Pada Siswa Kelas III Sekolah Dasar - Putri, Vera Zunita; Tabina , Melia Hansa Cordelia; Nisa , Sahda Aqila; Sanjaya, Elvona Agasthi Natarina; Fardani , Much Arsyad (Papanda, 2025)
This study aims to develop and test the feasibility of PAPEDA (Flat Shape Knowledge Board) learning media based on snakes and ladders game as a means to improve the understanding of third grade elementary school students on flat shape material. This study uses the Research and Development (R&D) method with the ADDIE development model consisting of five stages, namely: analysis, design, development, implementation, and evaluation. The subjects in this study were 10 third grade students of SD Negeri 2 Demaan and 1 class teacher. Validation was carried out by media experts and material experts, and practicality testing was carried out through student and teacher responses. Data collection techniques were carried out through expert validation and questionnaire distribution. The validation results showed that the media obtained a feasibility score of 90% from media experts and 92.5% from material experts with the category